Annual burning of semi‐natural grasslands for conservation favours tall‐grown species with high nectar production. (May 2018) - Milberg, Per; Fogelfors, Håkan; Westerberg, Lars; Tälle, Malin
Abstract : Species‐rich semi‐natural grasslands in Europe are a main target for conservation efforts, and alternative methods to the traditional management of mowing or grazing would be welcome due to the difficulties in maintaining traditional management practices. One such method proposed is burning of grassland vegetation during late winter or spring. To evaluate the effects of annual spring burning vs annual mowing on semi‐natural grassland vegetation, we compared the frequency of species in eleven field experiments in southern Sweden after ca 14 years. Out of the 88 species analyzed, five were more frequent in burnt plots compared with mowed plots ( Vicia cracca, Cirsium arvense, Urtica dioica, Galium verum, Convallaria majalis ). In contrast, 37 species were significantly less frequent in burnt plots compared with mowed ones, those with the largest differences being Ranunculus acris, Briza media, Veronica chamaedrys, Festuca ovina, Plantago lanceolata and Anthoxanthum odoratum . Tall‐grown species and those with preferences for N‐rich soils increased in frequency under an annual spring‐burn regime, compared with annual mowing, as did species producing larger amounts of nectar. Hence, although vegetation composition becomes more trivial with annual spring burns, there might be long‐term benefits for nectar‐feeding insects.